Economic and social influence of phenomenon brain gain and brain drain - Knězáčková, Radka; Procházková, Simona (SGEM, 2018)
The availability of high-quality and skilled workers is one of the basic prerequisites for the development of the country's economy, together with the technical level and equipment. States seek to promote the education and qualifications of their people. It is an investment in human capital. Human capital is unstable and can migrate, thus contributing to the economic development of other countries or regions (brain drain, brain gain). This phenomenon has not only demographic and sociological but also economic impacts. Problems associated with the phenomenon of brain drain can be described as the lack of human capital and the loss of public funds spent and provided for education. The acquired knowledge is applied in other country. The phenomenon of brain gain is a phenomenon where the state acquires skilled workers without having to spend public money on their education. The aim of this article is to identify areas of Europe that have the potential to draw educated migrants. Statistical methods will be used. The hypothesis that highly educated migrants come to countries with higher economic level will be verified. The results will be compared with public funds spent on the issue. As a result of population aging, migration and the ability of the country to attract migrants represent an important competitive advantage in terms of human labour and further development of the country and they are important for it.
Ekonomický a sociální dopad brain gain and brain drain
Keywords: brain drain; brain gain; migration; brain drain; brain gain; migrace